TEACHING EUCLIDEAN GEOMETRY AND INTRODUCING SOME NON-EUCLIDEAN GEOMETRIES: ENHANCING HIGH SCHOOL STUDENT ENGAGEMENT: https://doi.org/10.5281/zenodo.14235584 - Delan , Serhang; Bnar, Karim; Yusupova , R; Kobeeva , E.K.; Razbekova , A.I (International scientific and practical conference, 2024)
This study explores the impact of introducing non-Euclidean concepts within a high school Euclidean geometry curriculum to enhance student engagement and deepen understanding. By examining student behaviors and responses to non-Euclidean examples, we aim to assess the effectiveness of incorporating diverse geometric perspectives. The study employed a mixed-methods approach, with qualitative observations and quantitative assessments, to evaluate student engagement and comprehension changes. Findings indicate that integrating non-Euclidean geometries can foster curiosity and critical thinking, enriching the learning experience.